Desde la penumbra. Un retrato del exilio o la presencia de los cañaris en el Cusco - Crespo Toral, Hernán (Revista Española de Antropología Americana, 2003)
This paper studies the iconography of a picture in the Museo del Arzobispado in the city of Cusco. The picture, one of the Corpus Christi series, depicts the entrance of the Blessed Sacrament in the Cathedral. In the picture there are a group of Cañari Indians and a bit is blurred; in this fragment the Cañari chief Francisco Chilche probably exhibited the tzantza of an Inca warrior decapited.